Ontologies models cohesiveness: a first assessment of integration - Vitturini, Mercedes (2012)
Multiple ontologies over shared domain has been produced in the geographic ontology-design ﬁeld for GIS environments. In geneal, each GIS solution has its own data model or application ontology. Ontology model mapping could provide a common language from which several systems could exchange information in a semantic form. In this paper we present a novel technique that collaborates with the task of analyzing the degree of cohesion between ontologies and servers in order to anticipate the quality resulting from the integration process.